Efektivitas Model Problem Based Learning Berbantuan Media Audio Visual Terhadap Kemampuan Berpikir Kritis IPA Siswa Kelas V di MIN 2 Samarinda - Cahaya Purnama; Marniati Kadir; Rabiatul Adawiyah; Muhammad Subhan (PT. Berkah Smart Academica, 2024)
The background to the problem in this research is that the learning process often uses conventional models. The use of conventional models to improve students' critical thinking skills tends to be difficult, because these models are more teacher-centered, especially in the science learning process, teachers have not involved students directly so that students have not been trained in solving various existing problems and this causes students' critical thinking abilities to be less developed. . This research is quantitative research, using experimental methods with a quasi-experimental design type. The research design used is pretest posttest nonequivalent control group design. The results obtained are by looking at the average results of the pretest and posttest with the scores obtained in the experimental class, namely class V A, with an average pretest score of 42.13 and an average posttest score of 75.32. And the results of the average N-Gain score are 0.5744 in the medium category, which means that students' critical thinking abilities are further improved by using the problem based learning model assisted by audio-visual media. And the results of the t test after being given treatment obtained a sig (2-tailed) value of 0.003 < sig value 0.05, so the problem based learning model assisted by audio visual media is effective on the science critical thinking abilities of class V students at MIN 2 Samarinda.